Early detection of ocular abnormalities in a Chinese multicentre neonatal eye screening programme—1‐year result. Issue 3 (15th September 2020) - Fei, Ping; Liu, Zijiang; He, Liying; Li, Na; Xu, Lihua; Zhang, Meiju; Zhou, Yu; Li, Fuxin; Wang, Hong; Zhang, Qi; Huang, Qiujing; Li, Yi'an; et al.
Abstract: Purpose: Early detection of ocular abnormalities in newborns is essential for timely diagnosis and treatment. This study aimed to assess the 1‐year result of a multicentre prospective neonatal eye examination programme with wide‐field digital imaging system in China. Methods: A multicentre collaborative prospective study group for neonatal eye screening was established in nine hospitals, including eight Maternal and Children's Hospitals, and one general hospital across China from July 2016 to June 2017. Ocular examinations were performed on newborns within 28 days after birth using a wide‐field digital imaging system. Data were reviewed and analysed. The primary outcome was the prevalence of ocular abnormalities in neonates. Results: We detected 13 514 (20.91%) abnormal cases in 64 632 newborns. The most frequent abnormality was retinal haemorrhage (RH; 11.83%). Most of mild RH resolved spontaneously. Among those who were beyond retinopathy of prematurity (ROP) screening criteria of China (gestational age ≥32 w and birthweight ≥2000 g), the total number of neonates with ocular abnormality was 12 218/62 799(19.45%). 59.44% of neonatal ocular abnormalities detected (accounting for 11.56% of all the screened population) needed further interference or observation. Among them, 258 patients (0.41% of all the screened population) needed immediate or timely intervention, including congenital cataract, retinal detachment, retinoblastoma and other ocular abnormalities. One thousand and ninety‐eight patients (1.75% of all the screened neonates) should be followed up closely and needed further diagnosis or intervention if necessary, such as ROP or ROP‐like retinopathy, familial exudative vitreoretinopathy and persistent hyperplasia of primary vitreous. Five thousand nine hundred and six patients (9.4%) with minor clinical significance needed short‐term follow‐up. Conclusions: This prospective multicentre study of newborn ocular examination showed a relatively high prevalence of ocular abnormalities. There are a relatively high percentage of congenital eye pathology that required further referral and treatment in those neonates who were not screened routinely. According to the benefits and risks associated with neonatal eye examinations, neonatal ocular screening programme can detect ocular abnormalities at the very early stage and may play a positive role in promoting paediatric eye health.